Management considerations for a critically ill 26‐gestational week patient with COVID‐19: A case report - Khatib, Mohamad Y. (Clin Case Rep, 2021)
Pregnant women are potentially more susceptible to respiratory tract infections making them a high‐risk group. We describe the successful management of a 35‐year‐old pregnant woman, G3, P1, with a history of a cesarean section who tested positive for COVID‐19 at 26 weeks and required critical care support.